THE ROLE OF FINANCIAL DIGITIZATION IN IMPROVING BANKING PERFORMANCE FOR THE PERIOD 2020-2023: AN ANALYTICAL STUDY OF ASHUR INTERNATIONAL INVESTMENT BANK - Noor Abdulnabi Abboud (Scholars Digest Publishing, 2025)
The research aims to examine the role of financial digitization in improving banking performance at Ashur International Investment Bank. The research relied on modern technology, including financial digitization, to transform traditional financial services into digital forms. This digital development encompasses a wide range of services that rely on technology to reduce costs, improve efficiency, provide better user experiences, and increase financial inclusion. The research results showed that financial digitization has a significant negative impact on banking performance at Ashur International Investment Bank through an inverse relationship between the number of ATMs, total equity to total assets, and the rate of return on deposits. There is also an inverse relationship between the number of correspondent banking networks and the rate of return on deposits and a direct relationship between the number of correspondent banking networks and total equity to total assets. In light of this, the results are recommended. It is necessary to enhance banking services via the Internet to reduce costs and increase returns without resorting to expanding traditional banking structures.
Keywords: Financial digitization, banking performance, deposits, property rights, assets.